Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Bento Cafe Godean Yogyakarta - Rahman, Daipur; Prasetya, Bangun Putra (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
In company activities, human resources play a very dominant role. The success or failure of a company in achieving its goals really depends on the ability of its human resources or employees to carry out the tasks given. Therefore, all matters that include human resources must be an important concern for management so that employees have job satisfaction which is manifested in high work performance so that organizational goals can be achieved effectively and efficiently. In the bento cafe Godean Yogyakarta which was used as a sample in this research, there were only 10 employees. The data used in this research is primary data resulting from questionnaires distributed to respondents. The application program used by SPSS carries out instrument testing and data analysis. The instrument tests carried out in this research were validity tests and reliability tests. And the analysis used is the multiple linear analysis method, F test, t test and the type of research used in this research is associative type to determine the effect of the coefficient of determination R^2. Based on the research results, it can be concluded that the better and more conducive the organizational culture implemented at Bento Cafe Godean, the higher the level of job satisfaction felt by employees. The more conducive and comfortable the work environment at Bento Cafe Godean, both physically and non-physically, the higher the level of employee job satisfaction. These two factors, namely organizational culture and work environment, provide a strong contribution in increasing employee job satisfaction at Bento Cafe Godean.